Deep Sequencing of Cancer-Related Genes Revealed GNAS Mutations to Be Associated with Intraductal Papillary Mucinous Neoplasms and Its Main Pancreatic Duct Dilation - Takano, Shinichi (Public Library of Science, 2014)
BACKGROUND: To clarify the genetic mutations associated with intraductal papillary mucinous neoplasms (IPMN) and IPMN-related pancreatic tumours, we conducted cancer-related gene profiling analyses using pure pancreatic juice and resected pancreatic tissues. METHODS: Pure pancreatic juice was collected from 152 patients [nine with a normal pancreas, 22 with chronic pancreatitis (CP), 39 with pancreatic ductal adenocarcinoma (PDAC), and 82 with IPMN], and resected tissues from the pancreas were collected from 48 patients (six IPMNs and 42 PDACs). The extracted DNA was amplified by multiplexed polymerase chain reaction (PCR) targeting 46 cancer-related genes containing 739 mutational hotspots. The mutations were analysed using a semiconductor-based DNA sequencer. RESULTS: Among the 46 cancer-related genes, KRAS and GNAS mutations were most frequently detected in both PDAC and IPMN cases. In pure pancreatic juice, GNAS mutations were detected in 7.7% of PDAC cases and 41.5% of IPMN cases (p<0.001 vs. others). All PDAC cases with GNAS mutations (n = 3) were accompanied by IPMN. Multivariate analysis revealed that GNAS mutations in IPMN cases were associated with dilated main pancreatic ducts (MPD, p = 0.016), while no statistically independent associations with clinical variables were observed for KRAS mutations. In the resected pancreatic tissues, GNAS mutations were detected in 50% of PDAC cases concomitant with IPMN, 33.3% of PDAC cases derived from IPMN, and 66.7% of IPMN cases, while no GNAS mutations were detected in cases of PDAC without IPMN. CONCLUSIONS: The GNAS mutation was specifically found in the cases with IPMN and it was speculated that some PDACs might be influenced by the concomitant but separately-located IPMN in their pathogenic mechanism. Furthermore, the GNAS mutation was significantly associated with MPD dilatation in IPMN cases, suggesting its role in mucus hypersecretion.